Spore atlas of isosporate ferns of Punta Lara Nature Reserve, Argentina - Gorrer, Daniel Alejandro (2021)
Background and aims: The morphological characteristics of the spores provide information for the identification of fern taxa. To deepen the analyses of the morphological characteristics of the spores of the isosporated ferns inhabiting the Punta Lara Nature Reserve using light microscopy. M&M: The spores of the isosporate ferns that grow in the Punta Lara Nature Reserve (Buenos Aires Province, Argentina) were studied under a light microscope. The study was carried out with fresh materials collected during three years (2016-2018) at different sites of the Reserve. Twenty fern taxa, 16 native and 4 exotic, were analysed. The registered characteristics were: colour, shape, major and minor equatorial diameters, polar diameter, length and characteristics of the laesura and wall ornamentation. Results: The colour of the spores may be yellow, light brown, dark brown and only in Equisetum they are green (chlorophyllous). Most spores are monolete (13 species), other trilete (6 species) and only one species has alete spores. The spore walls may be smooth, wrinkled, folded, verrucated, tuberculated, reticulated and winged. Conclusions: The morphology of the spores allows the identification of the ferns of the Reserve at a generic and specific level and provides information for palaeopalynological and aeropalynological studies and of soil spore banks.